USERS’ INTENTION TO USE AN E WALLET INTEGRATED WITH E-HEALTH - Kelvin Yong Ming Lee; Pick Soon Ling; Mohamad Jais (International Journal of Accounting, Finance and Business, 2022)
This study proposed the integration of E-health function into the E-wallet. With theE-health function, users able to get the workout suggestion for the food purchased or consumedby them. This study extends the technology acceptance model (TAM) by including the socialmedia addiction as the potential factor. This study also successfully collected 240 responses.The findings confirm that perceived usefulness, perceived ease of use and social mediaaddiction are positively related to the attitude toward the integration of E-health function intoE-wallet. This attitude is also positively related with the user’s intention in using this proposednew function. The outcome of this study may serve as a guideline to enhance the existing Ewalletto attract the potential users. This study also recommends the E-wallet provider todeliver information through the social media. By using this way, E-wallet provider may alsoattract the potential users who are addicted to social media.